Meningkatkan Mutu Pendidikan Melalui Komite Madrasah - Ernadiati Ernadiati; Suswati Hendriani; Elda Herlina (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2022)
Madrasah could not erase the negative impression of "low quality schools" attached so far. The education quality improvement program has many problems at the application level, including the case of Muhammadiyah schools. One thing that supports or affects the quality of education is the madrasah committee. Therefore, this study aimed to determine the role of madrasah committees in improving the quality of education at the planning, implementation, and evaluation stages. This research can be categorized as qualitative research with a case study method. Qualitative descriptive data analysis techniques became the choice in this study. Based on the research, in general, the role of the madrasah committee is good. The committee runs according to what is expected. The madrasah committee carries out planning, implementation, and evaluation as a form of participation in advancing the quality of education in the madrasah.